PENGOLAHAN SAMPAH ORGANIK UNTUK MEWUJUDKAN BUDAYA SEKOLAH BERWAWASAN LINGKUNGAN DI SDN KANIGORO 03 KABUPATEN BLITAR - Ida Putriani; Eva Nurul Malahayati; Mar’atus Sholihah (LP2M Universitas Hasanuddin, 2022)
Waste accumulation is a common problem in the community, including in the school environment. This problem occurs due to school residents' lack of knowledge and expertise in recycling waste. This activity aims to provide knowledge and practice in processing organic waste in the school environment into compost and MOL. The activity at SDN Kanigoro 03 Blitar with target partners of 20 students and two teachers. The activity stages are 1) presentation and discussion of materials about the types of waste and their processing, and 2) group practicum to process organic waste. The result of this community dedication is that it can improve students' understanding and ability to recycle organic waste by 82.19. Students and teachers can process organic waste into compost and MOL, as shown from the results of the response questionnaire with an indicator reaction level of 87.33%, learning level of 91.5%, and behavior level of 88.67%, and result level of 97%. The conclusion is that the understanding of students and teachers in processing organic waste increases and can process organic waste into compost and MOL. — Penumpukan sampah di lingkungan sekolah menjadi masalah. Permasalahan ini terjadi akibat kurangnya pengetahuan dan keahlian warga sekolah dalam mengolah sampah, sehingga proses pengolahan sampah organik perlu dilakukan. Kegiatan ini bertujuan untuk memberikan pengetahuan dan praktek mengolah sampah organik di lingkungan sekolah menjadi pupuk kompos dan MOL. Kegiatan dilakukan di SDN Kanigoro 03 Kabupaten Blitar dengan mitra sasaran sebanyak 20 siswa dan 2 guru. Metode kegiatan yang digunakan yaitu 1) presentasi dan diskusi materi tentang jenis-jenis sampah dan pengolahannya, dan 2) praktikum secara berkelompok mengolah sampah organik. Hasil pengabdian ini menunjukkan pengetahuan siswa dan guru dalam pengolahan sampah organik sebesar 82,19. Siswa dan guru dapat mengolah sampah organik menjadi pupuk kompos dan MOL yang ditunjukkan dari hasil angket respon dengan indikator reaction level sebesar 87,33%, learning level sebesar 91,5%, behavior level sebesar 88,67%, dan result level sebesar 97%. Kesimpulannya adalah pemahaman siswa dan guru dalam mengolah sampah organik meningkat dan dapat mengolah sampah organik menjadi pupuk kompos dan MOL.